Meaning in Context and Contextual Meaning: A Perspective on the Semantics-Pragmatics Interface Applied to Modal Verbs - Ilse Depraetere (Anglophonia)
This paper argues for an approach to pragmatic meaning that hinges on the distinction between truth-conditional meaning and non-truth conditional meaning. While acknowledging that pragmatic processes (like saturation and ‘free pragmatic enrichment’) contribute as much to the recovery of the explicature or ‘what is said’ as pragmatic reasoning does to the recovery of implicated meaning, it is argued that a more elegant model is arrived at if it is truth-conditional content rather than pragmatic inference that is taken as a defining criterion of ‘pragmatics’ and related conceptual distinctions. First, a clear distinction needs to be made between a use of the term pragmatics which is more ‘formal’ in nature and which refers to the linguistic and non-linguistic context (‘meaning in context’) and one which is more ‘functional’ and which captures a specific type of meaning (‘contextual meaning’). This basic ‘form-function’ distinction is not always made explicit, and as a result, pragmatics becomes a very generic concept that refers to very diverse phenomena. In the terminological reflection that is presented here, pragmatics is restricted even further: it is reserved for non-truth conditional facets of contextual meaning, which are shown to encompass more than implicated meaning, while the truth-conditional facets of contextual meaning are situated in the realm of (context-dependent) semantics.